Using participatory action research to strengthen the socio-emotional intelligence competencies of a group of foundation phase learners in an informal settlement - Rawlins, Liza-Mari (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEdPsych)--Stellenbosch University, 2022.